People-powered Consulting : Enhancing Efficiency and Effectiveness in the Age of Generative AI - Lehký, Marek; Martínez, Felipe; Lobodáš, Pavel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis explores the impact of generative AI on the work of consultants and the consulting sector in general. The theoretical part of the thesis describes the basic concepts related to generative AI, its history and development, and its impact on the consulting sector. The empirical part uses qualitative and quantitative methods to assess the impact of AI on consultants' work performance. The results show that AI significantly enhances consultants' performance, especially in data processing and analysis tasks. The financial analysis shows that investment in AI yields a significant return on investment and increased profits. The paper also discusses the risks associated with integrating AI into consulting processes. Finally, the results of the analysis are summarized along with the formulation of specific recommendations for the proper adoption of AI in consulting firms so that AI functions as a tool to improve human performance and not as a substitute for human work. Overall, the paper provides important insights into the transformative potential of generative AI in consulting and outlines a path to its effective integration.
Vedoucí práce: Felipe Martínez
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses